Global health front-end medical device design: The use of prototypes to engage stakeholders. (2020) - Coulentianos, Marianna J.; Rodriguez-Calero, Ilka; Daly, Shanna R.; Sienko, Kathleen H.
Abstract: Availability, accessibility, affordability, and appropriateness are among several factors that significantly affect the adoption and diffusion of medical devices in low- and middle-income countries. Design processes that promote early and frequent engagement with stakeholders may increase the impact of medical devices aimed at addressing global health challenges by improving the uptake and sustained use of such devices. Prototypes are tools that can be leveraged to engage stakeholders during front-end design to define the problem, elicit requirements, and obtain feedback on early design concepts. Given the lack of literature that examines the practices for stakeholder engagement with prototypes during front-end design, this study was guided by the following research question: How do global health design practitioners approach stakeholder engagement with prototypes during front-end medical device design? Eleven design practitioners from industry were interviewed; transcripts were analyzed using thematic analysis to uncover prototyping behaviors. Transcript level counts of stakeholder groups, prototype forms, and strategies leveraged during stakeholder engagement with prototypes are reported. Based on the analysis of stakeholders, prototypes, and strategies, engagement events that reflect how the global health setting influenced decisions of stakeholder, prototype, and strategy are presented. Participants described challenges associated with: cross-cultural and remote design; the elicitation of contextual requirements; and limited access to resources. Participants devised approaches to overcome these challenges such as: engaging a wide range of stakeholders including proxy users and government stakeholders; developing long-term relationships with community partners; leveraging communication technologies; engaging stakeholders in the real use environment with physical prototypes; using prototypes to bridge the language barrier; 'polishing' prototypes; and inviting stakeholders to create and select prototypes. These results could impact approaches to practicing and teaching prototype usage during front-end design in a development setting. Highlights: Early design prototyping approaches for stakeholder engagement in LMICs were explored. Semi-structured interviews were conducted with 11 medical device designers. Rich cases of designers' approaches in global health settings are described. Cross-cultural design methodology and resource challenges were revealed. The study highlights practitioner approaches to overcome challenges.